Low-dosage high-performance admixture for mine filling and preparation method thereof
Patent Information
- Application Number
- CN202610846765.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-12
- Publication Date
- 2026-10-20
AI Technical Summary
[0007]鉴于此,本发明提出了一种低掺量型矿山充填专用高性能外加剂及其制备方法,旨在解决传统助剂掺量高、性能制衡、工况适配性差、耐久性不足的问题
本发明公开了一种低掺量型矿山充填专用高性能外加剂的制备方法,相较于传统矿山充填外加剂单一复配、性能制衡、掺量高、适配性差的技术缺陷,本发明创新构建无机微米晶核+多官能团有机聚合物外壳的核壳复合结构体系,结合钙硅前驱液原位反应改性、多元单体光照共聚、油水相高速剪切乳化一体化制备工艺,从微观水化机理、颗粒分散机制、界面结合强度、结构稳定性多维度突破传统技术瓶颈,实现低掺量、多功能、高稳定、强适配的综合技术优势。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of mine backfilling technology, and more specifically, to a low-dosage high-performance admixture for mine backfilling and its preparation method. Background Technology
[0002] With the rapid popularization of green mine construction and backfilling mining technology, cemented backfilling has become a core technical means for mine goaf management, tailings solid waste disposal, and ground pressure disaster control, possessing multiple values of resource recovery, ecological restoration, and safe production. The flow and transport properties, setting and hardening speed, mechanical strength, and volume stability of the backfill slurry directly determine the efficiency of mine backfilling construction, the quality of goaf backfilling, and the safety of mine operation. Admixtures, as key materials for regulating the workability and hardening properties of backfill slurry, can effectively improve the rheological properties of the slurry, optimize the setting regime, and enhance the strength of the backfill. They are key auxiliary materials for ensuring efficient and stable construction of mine backfilling projects and are currently widely used in various metal and non-metal mine backfilling projects.
[0003] Currently, the admixtures used in mine backfilling projects are mainly single-function additives such as ordinary water-reducing agents, early-strength agents, expanding agents, and water-retaining agents. Conventional products are mostly developed based on the conditions of building concrete, specifically adapted to ordinary cement-based cementitious materials, resulting in limited functionality and adaptability. Among the existing mainstream admixture systems, ordinary naphthalene-based and polycarboxylate-based water-reducing agents can only simply improve slurry fluidity, reduce slurry viscosity, and alleviate pipeline blockage problems; early-strength agents can only slightly improve the early strength of the backfill; and expanding agents are mainly used to improve shrinkage defects in the backfill and enhance the connection effect. To meet the needs of complex backfilling conditions, multiple admixtures are often required on-site to balance slurry fluidity, setting and hardening speed, and backfill stability.
[0004] However, existing mine backfill admixtures have revealed many unavoidable technical defects in practical engineering applications, highlighting significant pain points in the industry. Firstly, they suffer from high dosage, high cost, and poor economic efficiency. Traditional compound admixtures have low utilization rates of their effective components, generally requiring high dosages to achieve the desired modification effect, significantly increasing the cost of mine backfill materials and resulting in extremely poor economic efficiency in large-scale backfilling projects. Secondly, they exhibit poor performance synergy and performance balancing defects. Conventional admixtures cannot achieve synergistic optimization of fluidity, setting properties, and mechanical properties, generally exhibiting problems such as "increasing flow without enhancing strength, early strength easily shrinking, and expansion reducing strength." For example, while expansion agents can improve the shrinkage defects of the backfill, they easily disrupt the continuity of the matrix structure, leading to a significant decrease in the strength of the backfill at all ages, with the highest strength reduction reaching over 50%. Water-reducing agents, while improving slurry fluidity, easily cause slurry bleeding, segregation, and sedimentation problems, severely affecting the compaction of the backfill. Third, the admixtures have poor adaptability to working conditions and environmental conditions. Most existing admixtures are suitable for ambient temperature, pure cement-based backfill systems. However, mining sites present complex conditions such as low temperatures, high humidity, complex tailings composition, and large amounts of solid waste. Under low-temperature conditions, the modification effect of conventional admixtures is significantly reduced, and the early strength of the backfill can only reach 30% to 40% of that under ambient temperature conditions, severely restricting construction progress. For composite backfill systems using industrial solid wastes such as steel slag and fly ash, conventional admixtures have poor compatibility with cementitious materials and tailings aggregates, resulting in large fluctuations in modification effects and insufficient stability. Fourth, the admixtures lack durability and stability. Traditional admixtures have a simple component structure and cannot form a stable microstructure within the backfill. During long-term service, problems such as shrinkage cracking, strength reduction, and increased permeability coefficients easily occur, failing to meet the long-term safe backfill requirements of deep mines and high-stress goaf areas.
[0005] Delving into the root causes of the shortcomings of existing technologies, traditional mine backfill admixtures are mostly simple physical compound products. Their functional components are independent and lack chemical bonding, relying solely on physical adsorption to achieve modification effects. This results in inherent problems such as poor component compatibility, a single mechanism of action, and easy loss of effective components. Firstly, conventional admixtures lack multi-functional monomer copolymer modification structures, failing to simultaneously achieve multiple functions such as slurry dispersion, water retention, early strength, micro-expansion, and interface modification. The shortcomings of a single function cannot be compensated for by physical compounding, inevitably leading to a trade-off between various performance characteristics. Secondly, traditional products are not structurally designed for the solid-liquid interface characteristics of mine backfill systems, failing to effectively optimize the interfacial bonding state between tailings, solid waste aggregates, and cementitious materials. This results in poor slurry shear stability, making them prone to performance degradation and segregation under high-speed and long-distance transportation conditions. Secondly, existing preparation processes involve only simple mixing and compounding, lacking in-situ polymerization and precursor liquid modification and strengthening processes. This makes it impossible to construct a stable cross-linked network structure, resulting in low utilization of effective components in the additives. High dosages are required to meet engineering requirements, and the compatibility with low-temperature and complex aggregate conditions is extremely poor. Finally, conventional admixtures lack the support of a calcium-silicon composite modification system, making it impossible to simultaneously control the hydration reaction rate and morphology of hydration products in the filling system. This hinders the achievement of synergistic effects of rapid early hardening, steady later strength growth, and micro-volume expansion, and fails to fundamentally address core issues such as shrinkage, cracking, and insufficient strength of the filling body at the microscopic level.
[0006] In summary, the current field of mine backfilling urgently needs a special high-performance admixture with low dosage, multiple functions, high adaptability, and stable performance synergy to break through the technical bottlenecks of traditional admixtures, such as high dosage, performance balancing, poor adaptability to working conditions, and insufficient durability. Summary of the Invention
[0007] In view of this, the present invention proposes a low-dosage high-performance admixture for mine backfilling and its preparation method, aiming to solve the problems of high dosage, performance imbalance, poor adaptability to working conditions, and insufficient durability of traditional admixtures.
[0008] This invention proposes a method for preparing a low-dosage, high-performance admixture specifically for mine backfilling, comprising the following steps: An aqueous phase is obtained by mixing unsaturated carboxylic acid monomers, unsaturated polyether monomers, unsaturated sulfonic acid monomers, unsaturated hydroxyl monomers, unsaturated phosphoric acid monomers, and a photoinitiator with water. The oil phase is obtained by mixing the silane coupling agent with an organic solvent; Calcium nitrate, sodium hydroxide and water are mixed to obtain a calcium precursor solution; Sodium silicate, sodium hydroxide and water are mixed to obtain silicon precursor solution; After mixing the aqueous and oil phases, calcium and silicon precursor solutions are added, followed by high-speed shear emulsification and photopolymerization to obtain a low-dosage high-performance admixture for mine backfilling.
[0009] Preferably, the unsaturated carboxylic acid monomer includes one or more of acrylic acid, methacrylic acid, sodium methacrylate, hydroxyethyl acrylate, and maleic anhydride; The unsaturated polyether monomers include one or more of methoxy polyethylene glycol ether, allyl polyoxyethylene ether, isopentenyl polyoxyethylene ether, and methyl allyl polyoxyethylene ether.
[0010] Preferably, the unsaturated sulfonic acid monomers include one or more of sodium vinyl sulfonate, sodium allyl sulfonate, sodium methpropylene sulfonate, sodium p-styrene sulfonate, 2-acrylamido-2-methylpropanesulfonic acid, and ethyl methacrylate. The unsaturated hydroxyl monomers include one or more of hydroxyethyl acrylate, N-hydroxymethylacrylamide, hydroxybutyl vinyl ether, hydroxyethylacrylamide, and hydroxypropyl methacrylate.
[0011] Preferably, the unsaturated phosphate monomers include one or more of isopropenylphosphonic acid, vinylphosphonic acid, and hydroxyethyl methacrylate phosphate; The photoinitiator includes one or more of benzoin dimethyl ether, 4-acryloyl hydroxybenzoate benzophenone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, and sodium salt of (2,4,6-trimethylbenzoyl)diphenylphosphine oxide.
[0012] Preferably, the mass ratio of the unsaturated carboxylic acid monomer, unsaturated polyether monomer, unsaturated sulfonic acid monomer, unsaturated hydroxyl monomer, unsaturated phosphoric acid monomer, photoinitiator and water is 20:5~10:3~5:3~5:3~5:0.5~1:100~120.
[0013] Preferably, the mixing ratio of the silane coupling agent to the organic solvent is 5:10~15; The silane coupling agent includes one or more of N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane, N-β-aminoethyl-γ-aminopropylmethyldiethoxysilane, γ-mercaptopropylmethyldimethoxysilane, and bis-γ-triethoxysilyltetrasulfide. The organic solvent is selected from cyclohexane or hexane.
[0014] Preferably, the concentration of calcium nitrate in the calcium precursor solution is 15-20 g / L, and the pH value is 11-12; The concentration of sodium silicate in the silicon precursor solution is 15~20 g / L, and the pH value is 11~12.
[0015] Preferably, the volume ratio of the aqueous phase, oil phase, calcium precursor solution, and silicon precursor solution is 1000mL: 80~120mL: 500~800mL: 500~800mL; The high-speed shearing stirring rate is 10000~14000 r / min, and the time is 10~15 min; The photopolymerization process uses a xenon lamp for irradiation, with a light power density of 800~1000 mW / cm². 2 The irradiation time is 3 to 8 minutes, and the stirring is carried out at a rate of 500 to 600 r / min during the irradiation process.
[0016] This invention provides a low-dosage, high-performance admixture specifically for mine backfilling prepared by the above-described method.
[0017] This invention also provides the application of a low-dosage high-performance admixture for mine backfilling in mine backfilling.
[0018] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention discloses a method for preparing a low-dosage high-performance admixture for mine backfilling. Compared with the technical defects of traditional mine backfilling admixtures, such as single compounding, performance balancing, high dosage, and poor adaptability, this invention innovatively constructs a core-shell composite structure system of inorganic micron-sized crystal nuclei and multifunctional organic polymer shells. Combined with in-situ reaction modification of calcium-silicon precursor liquid, photopolymerization of multiple monomers, and integrated preparation process of high-speed shear emulsification of oil and water phases, this invention breaks through the traditional technical bottlenecks from multiple dimensions such as micro-hydration mechanism, particle dispersion mechanism, interfacial bonding strength, and structural stability, and achieves comprehensive technical advantages of low dosage, multifunctionality, high stability, and strong adaptability.
[0019] The inorganic micron-sized nuclei generated during the reaction of calcium and silicon precursor solutions can serve as hydration growth sites, effectively reducing the hydration nucleation barrier of cement clinker, significantly shortening the hydration induction period, and activating the early hydration activity of cement clinker.
[0020] This invention employs a multi-unsaturated monomer copolymerization to form a shell structure. The carboxyl group, as the core adsorption functional group, strongly adsorbs onto the surface of cement hydration particles and tailings aggregate particles, firmly locking the solid particles and providing a fundamental dispersion modification effect for the slurry system. The sulfonic acid and phosphonic acid groups possess extremely strong ionization capabilities, significantly enhancing the negative potential of the particle surface and generating high-intensity electrostatic repulsion, preventing the formation of agglomerates and flocculation structures. This allows for thorough slurry dispersion even at very low dosages, significantly reducing slurry viscosity, improving the fluidity and pumpability of the filling slurry, and making it suitable for long-distance, high-lift, and high-speed shear pipeline transportation conditions in mines. The hydroxyl group forms an excellent physical steric hindrance effect, creating a stable hydration protective film on the particle surface, effectively hindering collision, agglomeration, sedimentation, and stratification of solid particles, thus improving the uniformity and shear stability of the cementitious material system.
[0021] After hydrolysis, silane coupling agents can generate highly active silanol groups (-Si-OH), which can help construct steric structures and further improve the dispersion stability of slurry. On the other hand, they can react with the CSH gel particles generated by hydration and the hydroxyl groups on the surface of tailings aggregate to form stable Si-O-Si covalent chemical bonds, replacing the simple physical adsorption of traditional additives, so that the organic polymer shell and the inorganic hydration matrix and tailings aggregate form a strong overall cross-linked structure. Detailed Implementation
[0022] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention. It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the present invention.
[0023] Furthermore, regarding the numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Every smaller range between any stated value or intermediate value within a stated range, and any other stated value or intermediate value within said range, is also included within this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0024] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.
[0025] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.
[0026] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.
[0027] This invention proposes a method for preparing a low-dosage, high-performance admixture specifically for mine backfilling, comprising the following steps: An aqueous phase is obtained by mixing unsaturated carboxylic acid monomers, unsaturated polyether monomers, unsaturated sulfonic acid monomers, unsaturated hydroxyl monomers, unsaturated phosphoric acid monomers, and a photoinitiator with water. The oil phase is obtained by mixing the silane coupling agent with an organic solvent; Calcium nitrate, sodium hydroxide and water are mixed to obtain a calcium precursor solution; Sodium silicate, sodium hydroxide and water are mixed to obtain silicon precursor solution; After mixing the aqueous and oil phases, calcium and silicon precursor solutions are added, followed by high-speed shear emulsification and photopolymerization to obtain a low-dosage high-performance admixture for mine backfilling.
[0028] By synergistically combining calcium and silicon precursor solutions, a large amount of active Ca is precisely provided in the filling system. 2+ With SiO3 2- Active ions can generate a large number of ultrafine CSH gel microcrystals in situ under alkaline conditions, fundamentally optimizing the cement hydration kinetics process.
[0029] By employing a copolymerization system of unsaturated carboxylic acids, unsaturated polyethers, unsaturated sulfonic acids, unsaturated hydroxyl groups, and unsaturated phosphoric acid, multiple active functional groups are precisely grafted onto the polymer molecular chain to construct a multi-dimensional synergistic modification mechanism, which completely solves the defects of traditional admixtures such as single dispersion performance and easy bleeding and separation.
[0030] In this invention, the unsaturated carboxylic acid monomer includes one or more of acrylic acid, methacrylic acid, sodium methacrylate, hydroxyethyl acrylate, and maleic anhydride. In this invention, the unsaturated polyether monomer includes one or more of methoxy polyethylene glycol ether, allyl polyoxyethylene ether, isopentenyl polyoxyethylene ether, and methyl allyl polyoxyethylene ether.
[0031] In this invention, the unsaturated sulfonic acid monomers include one or more of sodium vinyl sulfonate, sodium allyl sulfonate, sodium methpropylene sulfonate, sodium p-styrene sulfonate, 2-acrylamido-2-methylpropanesulfonic acid, and ethyl methacrylate. In this invention, the unsaturated hydroxyl monomers include one or more of hydroxyethyl acrylate, N-hydroxymethylacrylamide, hydroxybutyl vinyl ether, hydroxyethylacrylamide, and hydroxypropyl methacrylate.
[0032] In this invention, the unsaturated phosphate monomers include one or more of isopropenylphosphonic acid, vinylphosphonic acid, and hydroxyethyl methacrylate phosphate. In this invention, the photoinitiator includes one or more of benzoin dimethyl ether, 4-acryloyl hydroxybenzoate benzophenone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, and sodium salt of (2,4,6-trimethylbenzoyl)diphenylphosphine oxide.
[0033] In this invention, the mass ratio of the unsaturated carboxylic acid monomer, unsaturated polyether monomer, unsaturated sulfonic acid monomer, unsaturated hydroxyl monomer, unsaturated phosphoric acid monomer, photoinitiator and water is 20:5~10:3~5:3~5:3~5:0.5~1:100~120.
[0034] In this invention, the mixing ratio of the silane coupling agent to the organic solvent is 5:10~15.
[0035] In this invention, the silane coupling agent includes one or more of N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane, N-β-aminoethyl-γ-aminopropylmethyldiethoxysilane, γ-mercaptopropylmethyldimethoxysilane, and bis-γ-triethoxysilylpropyltetrasulfide. The silane coupling agents selected in this invention are all bifunctional silane coupling agents, which can provide a good bridging effect.
[0036] The organic solvent is selected from cyclohexane or hexane.
[0037] In this invention, the concentration of calcium nitrate in the calcium precursor solution is 15-20 g / L, and the pH value is 11-12. In this invention, the concentration of sodium silicate in the silicon precursor solution is 15-20 g / L, and the pH value is 11-12.
[0038] In this invention, the volume ratio of the aqueous phase, oil phase, calcium precursor solution, and silicon precursor solution is 1000mL: 80~120mL: 500~800mL: 500~800mL; In this invention, the stirring rate of the high-speed shearing is 10000~14000 r / min, and the time is 10~15 min; In this invention, the photopolymerization is performed using a xenon lamp with a light power density of 800~1000 mW / cm². 2 The irradiation time is 3 to 8 minutes, and the stirring is carried out at a rate of 500 to 600 r / min during the irradiation process.
[0039] This invention provides a low-dosage, high-performance admixture specifically for mine backfilling prepared by the above-described method.
[0040] This invention also provides the application of a low-dosage high-performance admixture for mine backfilling in mine backfilling.
[0041] Example 1 1) Preparation of aqueous phase: Unsaturated carboxylic acid monomer (acrylic acid), unsaturated polyether monomer (allyl polyoxyethylene ether), unsaturated sulfonic acid monomer (sodium p-styrene sulfonate), unsaturated hydroxyl monomer (hydroxypropyl methacrylate), unsaturated phosphoric acid monomer (isopropenylphosphonic acid), photoinitiator (benzoin dimethyl ether) and water are mixed in a mass ratio of 20:8:4:4:4:0.8:110 and stirred evenly to obtain an aqueous phase; 2) Preparation of the oil phase: The silane coupling agent (γ-mercaptopropylmethyldimethoxysilane) and the organic solvent (cyclohexane) are mixed at a ratio of 5:10 and stirred until uniformly dissolved to obtain the oil phase; 3) Preparation of calcium precursor solution: Mix calcium nitrate, sodium hydroxide and water to prepare a calcium precursor solution with a calcium nitrate concentration of 15 g / L and a pH value of 12; 4) Preparation of silicon precursor solution: Sodium silicate, sodium hydroxide and water are mixed to prepare a silicon precursor solution with a sodium silicate concentration of 15 g / L and a pH value of 12; 5) Mix the above aqueous phase and oil phase, then add calcium precursor solution and silicon precursor solution at a volume ratio of 1000mL:100mL:700mL:600mL, and then emulsify at high speed of 10000r / min for 10min; then use a light power density of 800mW / cm². 2 Xenon lamps were used for photopolymerization, with an irradiation time of 5 minutes. During the irradiation process, the mixture was stirred at a rate of 550 r / min. After the reaction was completed, the mixture was cooled and allowed to stand, thus obtaining a low-dosage high-performance admixture for mine backfilling.
[0042] Example 2 1) Preparation of aqueous phase: Unsaturated carboxylic acid monomer (methacrylic acid), unsaturated polyether monomer (methoxy polyethylene glycol ether), unsaturated sulfonic acid monomer (sodium allyl sulfonate), unsaturated hydroxyl monomer (hydroxyethyl acrylate), unsaturated phosphoric acid monomer (vinylphosphonic acid), photoinitiator ((2,4,6-trimethylbenzoyl)diphenylphosphine oxide sodium salt) and water are mixed in a mass ratio of 20:5:5:5:5:1:120 and stirred evenly to obtain an aqueous phase; 2) Preparation of the oil phase: The silane coupling agent (N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane) and the organic solvent (hexane) are mixed in a ratio of 5:10 and stirred until uniformly dissolved to obtain the oil phase; 3) Preparation of calcium precursor solution: Mix calcium nitrate, sodium hydroxide and water to prepare a calcium precursor solution with a calcium nitrate concentration of 17 g / L and a pH value of 11.6; 4) Preparation of silicon precursor solution: Sodium silicate, sodium hydroxide and water are mixed to prepare a silicon precursor solution with a sodium silicate concentration of 18 g / L and a pH value of 11.8; 5) Mix the above aqueous and oil phases, then add calcium and silicon precursor solutions at a volume ratio of 1000 mL: 110 mL: 750 mL: 650 mL. Then, perform high-speed shear emulsification at 11000 r / min for 10 min. Finally, use an optical power density of 1000 mW / cm². 2 Xenon lamps were used for photopolymerization, with an irradiation time of 8 minutes. During the irradiation process, the mixture was stirred at a rate of 500 r / min. After the reaction was completed, the mixture was cooled and allowed to stand, thus obtaining a low-dosage high-performance admixture for mine backfilling.
[0043] Example 3 1) Preparation of aqueous phase: Unsaturated carboxylic acid monomer (hydroxyethyl acrylate), unsaturated polyether monomer (methyl allyl polyoxyethylene ether), unsaturated sulfonic acid monomer (2-acrylamido-2-methylpropanesulfonic acid), unsaturated hydroxyl monomer (hydroxyethyl acrylamide), unsaturated phosphoric acid monomer (hydroxyethyl methacrylate phosphate), photoinitiator (2-hydroxy-2-methyl-1-phenyl-1-propanone) and water are mixed in a mass ratio of 20:10:3:3:3:0.5:100 and stirred evenly to obtain an aqueous phase; 2) Preparation of the oil phase: The silane coupling agent (N-β-aminoethyl-γ-aminopropylmethyldiethoxysilane) and the organic solvent (cyclohexane) are mixed at a ratio of 5:10 and stirred until uniformly dissolved to obtain the oil phase; 3) Preparation of calcium precursor solution: Mix calcium nitrate, sodium hydroxide and water to prepare a calcium precursor solution with a calcium nitrate concentration of 20 g / L and a pH value of 11.4; 4) Preparation of silicon precursor solution: Sodium silicate, sodium hydroxide and water are mixed to prepare a silicon precursor solution with a sodium silicate concentration of 17 g / L and a pH value of 11.9; 5) Mix the above aqueous and oil phases, then add calcium and silicon precursor solutions at a volume ratio of 1000 mL: 80 mL: 800 mL: 800 mL. Then, perform high-speed shear emulsification at 12000 r / min for 15 min. Finally, use an optical power density of 900 mW / cm². 2 Xenon lamps were used for photopolymerization, with an irradiation time of 3 minutes. During the irradiation process, the mixture was stirred at a rate of 600 r / min. After the reaction was completed, the mixture was cooled and allowed to stand, thus obtaining a low-dosage high-performance admixture for mine backfilling.
[0044] Example 4 1) Preparation of aqueous phase: Unsaturated carboxylic acid monomer (maleic anhydride), unsaturated polyether monomer (isoprene alcohol polyoxyethylene ether), unsaturated sulfonic acid monomer (sodium methacrylate), unsaturated hydroxyl monomer (N-hydroxymethylacrylamide), unsaturated phosphoric acid monomer (vinylphosphonic acid), photoinitiator (4-acryloylhydroxybenzoic acid benzophenone) and water are mixed in a mass ratio of 20:7:4.5:3.5:3.5:0.7:115 and stirred evenly to obtain an aqueous phase; 2) Preparation of oil phase: The silane coupling agent (bis-γ-triethoxysilylpropyltetrasulfide) and the organic solvent (hexane) are mixed in a ratio of 5:10 and stirred until uniformly dissolved to obtain the oil phase; 3) Preparation of calcium precursor solution: Mix calcium nitrate, sodium hydroxide and water to prepare a calcium precursor solution with a calcium nitrate concentration of 16 g / L and a pH value of 12; 4) Preparation of silicon precursor solution: Sodium silicate, sodium hydroxide and water are mixed to prepare a silicon precursor solution with a sodium silicate concentration of 19 g / L and a pH value of 12; 5) Mix the above aqueous phase and oil phase, then add calcium precursor solution and silicon precursor solution at a volume ratio of 1000mL:115mL:650mL:750mL, and then emulsify at high speed of 10000r / min for 10min; then use an optical power density of 900mW / cm². 2 Xenon lamps were used for photopolymerization, with an irradiation time of 5 minutes. During the irradiation process, the mixture was stirred at a rate of 550 r / min. After the reaction was completed, the mixture was cooled and allowed to stand, thus obtaining a low-dosage high-performance admixture for mine backfilling.
[0045] Example 5 1) Preparation of aqueous phase: Unsaturated carboxylic acid monomer (sodium methpropylene sulfonate), unsaturated polyether monomer (allyl polyoxyethylene ether), unsaturated sulfonic acid monomer (ethyl methacrylate), unsaturated hydroxyl monomer (hydroxyethyl acrylate), unsaturated phosphoric acid monomer (isopropenylphosphonic acid), photoinitiator (benzoin dimethyl ether) and water are mixed in a mass ratio of 20:6:3.5:4.5:4.5:0.9:105 and stirred evenly to obtain an aqueous phase; 2) Preparation of the oil phase: The silane coupling agent (γ-mercaptopropylmethyldimethoxysilane) and the organic solvent (cyclohexane) are mixed at a ratio of 5:10 and stirred until uniformly dissolved to obtain the oil phase; 3) Preparation of calcium precursor solution: Mix calcium nitrate, sodium hydroxide and water to prepare a calcium precursor solution with a calcium nitrate concentration of 19 g / L and a pH value of 12; 4) Preparation of silicon precursor solution: Sodium silicate, sodium hydroxide and water are mixed to prepare a silicon precursor solution with a sodium silicate concentration of 17 g / L and a pH value of 12; 5) Mix the above aqueous phase and oil phase, then add calcium precursor solution and silicon precursor solution at a volume ratio of 1000mL:95mL:800mL:500mL, and then emulsify at high speed of 13000r / min for 13min; then use a light power density of 850mW / cm². 2 Xenon lamps were used for photopolymerization, with an irradiation time of 5 minutes. During the irradiation process, the mixture was stirred at a rate of 550 r / min. After the reaction was completed, the mixture was cooled and allowed to stand, thus obtaining a low-dosage high-performance admixture for mine backfilling.
[0046] Comparative Example 1 1) Preparation of aqueous phase: Unsaturated carboxylic acid monomer (acrylic acid), unsaturated polyether monomer (allyl polyoxyethylene ether), unsaturated sulfonic acid monomer (sodium p-styrene sulfonate), unsaturated hydroxyl monomer (hydroxypropyl methacrylate), unsaturated phosphoric acid monomer (isopropenylphosphonic acid), photoinitiator (benzoin dimethyl ether) and water are mixed in a mass ratio of 20:8:4:4:4:0.8:110 and stirred evenly to obtain an aqueous phase; 2) Preparation of calcium precursor solution: Mix calcium nitrate, sodium hydroxide and water to prepare a calcium precursor solution with a calcium nitrate concentration of 15 g / L and a pH value of 12; 3) Preparation of silicon precursor solution: Sodium silicate, sodium hydroxide and water are mixed to prepare a silicon precursor solution with a sodium silicate concentration of 15 g / L and a pH value of 12; 4) Mix the above aqueous phase with the calcium precursor solution and silicon precursor solution at a volume ratio of 1000 mL: 700 mL: 600 mL, then shear and stir at a high speed of 10000 r / min for 10 min; then use an optical power density of 800 mW / cm². 2 Xenon lamps were used for photopolymerization, with an irradiation time of 5 minutes. During the irradiation process, the mixture was stirred at a rate of 550 r / min. After the reaction was completed, the mixture was cooled and allowed to stand, thus obtaining a low-dosage high-performance admixture for mine backfilling.
[0047] The only difference between this comparative example and Example 1 is that the addition of the silane coupling agent is omitted.
[0048] Comparative Example 2 1) Preparation of aqueous phase: Unsaturated carboxylic acid monomer (acrylic acid), photoinitiator (benzoin dimethyl ether) and water are mixed at a mass ratio of 40:0.8:110 and stirred evenly to obtain an aqueous phase; 2) Preparation of the oil phase: The silane coupling agent (γ-mercaptopropylmethyldimethoxysilane) and the organic solvent (cyclohexane) are mixed at a ratio of 5:10 and stirred until uniformly dissolved to obtain the oil phase; 3) Preparation of calcium precursor solution: Mix calcium nitrate, sodium hydroxide and water to prepare a calcium precursor solution with a calcium nitrate concentration of 15 g / L and a pH value of 12; 4) Preparation of silicon precursor solution: Sodium silicate, sodium hydroxide and water are mixed to prepare a silicon precursor solution with a sodium silicate concentration of 15 g / L and a pH value of 12; 5) Mix the above aqueous phase and oil phase, then add calcium precursor solution and silicon precursor solution at a volume ratio of 1000mL:100mL:700mL:600mL, and then emulsify at high speed of 10000r / min for 10min; then use a light power density of 800mW / cm². 2 Xenon lamps were used for photopolymerization, with an irradiation time of 5 minutes. During the irradiation process, the mixture was stirred at a rate of 550 r / min. After the reaction was completed, the mixture was cooled and allowed to stand, thus obtaining a low-dosage high-performance admixture for mine backfilling.
[0049] The difference between this comparative example and Example 1 is that only unsaturated carboxylic acid monomers are added.
[0050] The performance of the admixtures prepared in Examples 1-5 and Comparative Examples 1-2 was tested using the following methods: Prepare the following cement mortar for mine filling according to the following mass proportions: 25 parts coarse tailings (particle size > 0.5 mm), 20 parts fine tailings (0.05 mm < particle size < 0.1 mm), 3 parts silicate cement, 20 parts steel slag, 10 parts fly ash, 10 parts gypsum, 1 part admixture, and 40 parts water; According to the "Technical Standard for Backfilling Engineering in Metal and Non-metal Mines" (GB / T51450-2022), the performance of the above-mentioned cement mortar was tested, and the test results are as follows: As can be seen from the data in Table 1, the admixture-modified mortars prepared in each embodiment exhibit excellent overall flowability, uniform slurry rheological properties, and good flow stabilization effect. Compared with Comparative Example 1, which lacks a silane coupling agent, and Comparative Example 2, which is modified with only a single monomer, the slurry slump, spread, and flowability values of the embodiments are more balanced, without excessive flow or bleeding segregation problems. This effectively solves the defects of traditional admixtures that easily lead to slurry thinning, stratification, and pipeline blockage, and fully meets the pipeline transportation construction requirements of long-distance, high-lift, and high-speed shearing in mines.
[0051] In addition, the admixture-modified mortar prepared in each embodiment has an appropriate setting time, which avoids the problems of pipe blockage and insufficient construction operation time caused by excessively rapid setting, and also eliminates the hidden dangers of delayed filling body formation, extended construction cycle and untimely support of goaf caused by excessively slow setting, perfectly matching the standardized construction rhythm of mine filling.
[0052] The 28-day uniaxial compressive strength of the filling mortar in each embodiment reached 4.5~4.9 MPa, far exceeding the 3.0~3.2 MPa of the comparative example, demonstrating a significant improvement in mechanical properties. Thanks to the core-shell composite structure and calcium-silicon in-situ modification system of this invention, the hydration products of the filling body have a dense structure, effectively solving the performance trade-off problem of traditional admixtures—"increasing flow without enhancing strength, and early strength easily shrinking"—ensuring the structural strength and long-term stability of the filling body, and effectively meeting the engineering bearing requirements for goaf control, solid waste disposal, and ecological restoration.
[0053] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that modifications or equivalent substitutions can still be made to the specific implementation of the present invention. Any modifications or equivalent substitutions that do not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a low-dosage, high-performance admixture specifically for mine backfilling, characterized in that, Includes the following steps: An aqueous phase is obtained by mixing unsaturated carboxylic acid monomers, unsaturated polyether monomers, unsaturated sulfonic acid monomers, unsaturated hydroxyl monomers, unsaturated phosphoric acid monomers, and a photoinitiator with water. The oil phase is obtained by mixing the silane coupling agent with an organic solvent; Calcium nitrate, sodium hydroxide and water are mixed to obtain a calcium precursor solution; Sodium silicate, sodium hydroxide and water are mixed to obtain silicon precursor solution; After mixing the aqueous and oil phases, calcium and silicon precursor solutions are added, followed by high-speed shear emulsification and photopolymerization to obtain a low-dosage high-performance admixture for mine backfilling.
2. The preparation method of a low-dosage high-performance admixture for mine backfilling according to claim 1, characterized in that, The unsaturated carboxylic acid monomer includes one or more of acrylic acid, methacrylic acid, sodium methacrylate, hydroxyethyl acrylate, and maleic anhydride; The unsaturated polyether monomers include one or more of methoxy polyethylene glycol ether, allyl polyoxyethylene ether, isopentenyl polyoxyethylene ether, and methyl allyl polyoxyethylene ether.
3. The preparation method of a low-dosage high-performance admixture for mine backfilling according to claim 1, characterized in that, The unsaturated sulfonic acid monomers include one or more of sodium vinyl sulfonate, sodium allyl sulfonate, sodium methpropylene sulfonate, sodium p-styrene sulfonate, 2-acrylamido-2-methylpropanesulfonic acid, and ethyl methacrylate. The unsaturated hydroxyl monomers include one or more of hydroxyethyl acrylate, N-hydroxymethylacrylamide, hydroxybutyl vinyl ether, hydroxyethylacrylamide, and hydroxypropyl methacrylate.
4. The preparation method of a low-dosage high-performance admixture for mine backfilling according to claim 1, characterized in that, The unsaturated phosphate monomers include one or more of isopropenylphosphonic acid, vinylphosphonic acid, and hydroxyethyl methacrylate phosphate. The photoinitiator includes one or more of benzoin dimethyl ether, 4-acryloyl hydroxybenzoate benzophenone, 2-hydroxy-2-methyl-1-phenyl-1-propanone, and sodium salt of (2,4,6-trimethylbenzoyl)diphenylphosphine oxide.
5. The preparation method of a low-dosage high-performance admixture for mine backfilling according to claim 1, characterized in that, The mass ratio of the unsaturated carboxylic acid monomer, unsaturated polyether monomer, unsaturated sulfonic acid monomer, unsaturated hydroxyl monomer, unsaturated phosphoric acid monomer, photoinitiator and water is 20:5~10:3~5:3~5:3~5:0.5~1:100~120.
6. The preparation method of a low-dosage high-performance admixture for mine backfilling according to claim 1, characterized in that, The mixing ratio of the silane coupling agent to the organic solvent is 5:10~15; The silane coupling agent includes one or more of N-β-aminoethyl-γ-aminopropylmethyldimethoxysilane, N-β-aminoethyl-γ-aminopropylmethyldiethoxysilane, γ-mercaptopropylmethyldimethoxysilane, and bis-γ-triethoxysilyltetrasulfide. The organic solvent is selected from cyclohexane or hexane.
7. The preparation method of a low-dosage high-performance admixture for mine backfilling according to claim 1, characterized in that, The concentration of calcium nitrate in the calcium precursor solution is 15-20 g / L, and the pH value is 11-12. The concentration of sodium silicate in the silicon precursor solution is 15~20 g / L, and the pH value is 11~12.
8. The preparation method of a low-dosage high-performance admixture for mine backfilling according to claim 1, characterized in that, The volume ratio of the aqueous phase, oil phase, calcium precursor solution, and silicon precursor solution is 1000mL: 80~120mL: 500~800mL: 500~800mL; The high-speed shearing stirring rate is 10000~14000 r / min, and the time is 10~15 min; The photopolymerization process uses a xenon lamp for irradiation, with a light power density of 800~1000 mW / cm². 2 The irradiation time is 3 to 8 minutes, and the stirring is carried out at a rate of 500 to 600 r / min during the irradiation process.
9. The low-dosage high-performance admixture for mine backfilling prepared by the preparation method of any one of claims 1 to 8.
10. The application of the low-dosage high-performance admixture for mine backfilling as described in claim 9 in mine backfilling.